Suriana maritima Bay Cedar: FPS-565/FP565, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Suriana maritima, commonly known as Bay Cedar. It describes the plant’s characteristics, including its sturdy, branched trunk, dark brown flaky bark, and tiny gray-green leaves. The document highlights the plant’s yellow, cup-shaped flowers that bloom throughout the year and its small, brown, five-pointed calyx that holds the seeds. It also covers the plant’s growth habits, preferred growing conditions, and uses in landscaping, such as hedges, mass plantings, and buffer strips. Additionally, it addresses the plant’s high tolerance for salt and wind, making it ideal for coastal landscapes. Original publication date October 1999.